Differential expression of microRNAs in peripheral B lymphocytes in patients with IgA nephropathy and its clinical significance - WANG Qian-liao; CHEN Ting-yu; LI Gui-sen; WANG Li (Linchuang shenzangbing zazhi)
Objective The aberrantly glycosylated IgA1 plays a crucial role in the pathogenesis of IgA nephropathy.In this study,we firstly identified the microRNAs expression profiles from peripheral blood B lymphocytes,and validated the differentially expressed candidate microRNAs in IgA nephropathy patients and healthy controls.Then we analyzed the relationship between the expression levels of these microRNAs with clinical parameters,pathological manifestations and serum aberrantly O-glycosylated IgA1 level.Methods CD19~+ B lymphocytes were isolated by Dynabeads CD19 magnetic beads from 7 IgA nephropathy patients and 4 healthy controls.Then the total RNA was extracted and the differential expression of microRNAs was detected by miRCURY LNA Array(v.18.0).Five candidate microRNAs were validated by QRT-PCR in 16 healthy controls and 29 IgA nephropathy patients.The relationships between expression levels of the five microRNAs and clinical-pathological parameters as well as serum galactose-deficient IgA1(Gd-IgA1) were analyzed.Results As compared with healthy controls,there were 115 significantly differentially expressed microRNAs in patients with IgA nephropathy,in which 85 upregulated and 30 downregulated.Five microRNAs,miR-3189-5p,let-7g-5p,miR-4258-5p,miR-4695-3p and miR-99b-5p were selected as candidates for further validation.The expression levels of the 5 candidate microRNAs showed no statistically significant different between IgA nephropathy patients and healthy controls.There was no statistically significant correlation between the expression levels of the 5 microRNAs and the clinicopathological parameters.The serum level of Gd-IgA1 in IgA nephropathy patients was significantly higher than in healthy controls.But there was no significant association between expression level of each microRNA and serum GdIgA1 level.Conclusions The microRNAs’ expression profile of peripheral blood B lymphocytes in IgA nephropathy patients was significantly different from healthy controls.Validation study showed that the expression of the five candidate microRNAs(miR-3189-5p,let-7g-5p,miR-4258-5p,miR-4695-3p and miR-99b-5p) weren’t significantly different between IgA nephropathy patients and healthy controls,and there was no significant association between the expression levels of the five microRNAs and clinicopathological parameters,as well as Gd-IgA1 level.It suggested that the five microRNAs might not be the crucial molecules for production of Gd-IgA1.